Некоторые сведения о пелопее обыкновенном — Sceliphron destillatorium Кl. (Sphecidae, Hymenoptera) - Миноранский, В.А.; Харченко, В.И.; Фомичев, А.И. (Вестник зоологии, 1970)
Описывается экология пелопея обыкновенного (Sceliphron destillatorium К l.) в степной зоне Европейской части СССР, перечисляются его враги. Sceliphron destillatorium К I. is widely distributed species of the steppe and, partially, forest-steppe zones of the European part of the USSR. Being a south species as to
the origin, it could settle in the north direction owing to the transition to synanthropic
mode of life. In the European part of the USSR ways of accilimatization at low temperatures are: building of nets on chimneys of flues and others, in places well warmed up in
winter, as well as long diapause of larva of the last age, going to wintering in cocoon.
Different species of paralysed spiders serve as food for larvae. Their quantity in a
separate cell fluctuates within the limits 3—5 (often 4—6) individuals, and weight,
330—350 mg.
In the nests of S. destillatorium H l. larvae of Amobia distorta Alle n occur, feeding on spiders prepared by wasp. Alternation of generations in Amobia distorta Alle n
coincides with those in wasp. From the secondary dwellers of Sceliphron destillatorium
H I. the bee Osmia aenea L. was found. The organic residua remained in the cells are
obliterated by Frogoderma glabrum Hebst and Anthrenus pobonicus Mr.